Pointing in the right direction. A discussion of The evolution of social communication in primates, eds. M. Pina and N. Gontier - Dębska, Agnieszka (Theoria et Historia Scientiarum, 2015)
The Evolution of Social Communication in Primates, edited by Marco Pina and Natalie Gontier is an important contribution to the current debates on language evolution. The volume includes texts discussing the emergence of basic social skills connected with language, arguments for vocal and gestural protolanguage, and theories of development of symbolic and compositional language in the history of humanity. In this review, I present the structure and content of the book, but also highlight issues that reflect key controversies in this research area, such as the transition from gestures to speech and from simple vocalizations to modern language. I discuss one specific issue, pointing in nonhuman primates and human children, to offer some remarks on theoretical and empirical criteria for using psychological concepts in debates on social communication in primates.